Chronic postsurgical pain in Europe. Issue 10 (October 2015) - Fletcher, Dominique; Stamer, Ulrike M.; Pogatzki-Zahn, Esther; Zaslansky, Ruth; Tanase, Narcis Valentin; Perruchoud, Christophe; Kranke, Peter; Komann, Marcus; Lehman, Thomas; Meissner, Winfried
<x xml:space="preserve">Abstract</x> BACKGROUND Chronic postsurgical pain (CPSP) is an important clinical problem. Prospective studies of the incidence, characteristics and risk factors of CPSP are needed. OBJECTIVES The objective of this study is to evaluate the incidence and risk factors of CPSP. DESIGN A multicentre, prospective, observational trial. SETTING Twenty-one hospitals in 11 European countries. PATIENTS Three thousand one hundred and twenty patients undergoing surgery and enrolled in the European registry PAIN OUT. MAIN OUTCOME MEASURES Pain-related outcome was evaluated on the first postoperative day (D1) using a standardised pain outcome questionnaire. Review at 6 and 12 months via e-mail or telephonic interview used the Brief Pain Inventory (BPI) and the DN4 (Douleur Neuropathique four questions). Primary endpoint was the incidence of moderate to severe CPSP (numeric rating scale, NRS ≥3/10) at 12 months. RESULTS For 1044 and 889 patients, complete data were available at 6 and 12 months. At 12 months, the incidence of moderate to severe CPSP was 11.8% (95% CI 9.7 to 13.9) and of severe pain (NRS ≥6) 2.2% (95% CI 1.2 to 3.3). Signs of neuropathic pain were recorded in 35.4% (95% CI 23.9 to 48.3) and 57.1% (95% CI 30.7 to 83.4) of patients with moderate and severe CPSP, respectively. Functional impairment (BPI) at 6 and 12 months increased with the severity of CPSP (P < 0.01) and presence of neuropathic characteristics (P < 0.001). Multivariate analysis identified orthopaedic surgery, preoperative chronic pain and percentage of time in severe pain on D1 as risk factors. A 10% increase in percentage of time in severe pain was associated with a 30% increase of CPSP incidence at 12 months. CONCLUSION The collection of data on CPSP was feasible within the European registry PAIN OUT. The incidence of moderate to severe CPSP at 12 months was 11.8%. Functional impairment was associated with CPSP severity and neuropathic characteristics. Risk factors for CPSP in the present study were chronic preoperative pain, orthopaedic surgery and percentage of time in severe pain on D1. TRIAL REGISTRATION Clinicaltrials.gov identifier: NCT01467102.